AS IMPLICAÇÕES DA REORGANIZAÇÃO DO ESTADO BRASILEIRO (A PARTIR DOS ANOS 1990) NOS PROCESSOS DE PLANEJAMENTO DA EDUCAÇÃO BRASILEIRA E O CONTROLE SOCIAL: O CASO DO PLANO MUNICIPAL DE CARAMBEÍ (PR) /2006 - LUZ, ANGELO JULIANO CARNEIRO (2014)
Marxist studies, related to the formation of public policies in Brazil, especially after the 1990s, including those developed by Valente (2000), Saviani (2004) and Lima (2011), have focused their analysis on the contribution of economic reforms derived from neoliberal policies and international agreements made effective among States and representatives of global capitalism. Being this discussion relevant, we show in this paper considerations concerning the elaboration of the National Plan for Education and the strong presence of international agencies of the guidelines in this scenario, with emphasis on the participatory status of civil society in social control of the educational activities organized by the State. When considering the structural issues related to the determinants that make up the definitions of national policy, the guiding theoretical support of the exhibition is based on the historical materialist dialectics as a method of analysis, interpretation and reproduction in ideal plan, of the decisions and policy referrals made by the Brazilian government (Netto, 2011). Thus, the categories of class struggle and civil society, alluded to by Marx and Engels (1991) and Gramsci (1984) respectively, are presented as key elements to guide the analysis of reality, ie, the process of consolidating Brazilian educational policies. In search of the unveiling of the real implications and positions that depart from the State and the subjects facing the primary task of building control and planning of municipal education policy, we have as objective in this research to analyze the process of drafting the Municipal Education Plan Carambeí, in the context of the Brazilian national planning, seeking to notice the participation and social control of it. From the literature survey, official documents and semi-structured interviews conducted with the subjects involved in the drafting of the Municipal Plan of Education of the City of Carambeí process - PR, and relevant analysis to knowledge movement effected by the dictates of the capitalist system political organization of the State, it was provided an opportunity to present the findings of mediations and coping in the position of civil society in relation to social control of the municipal educational policy. Therefore, in order to organize textually conducted research, this study is divided into three chapters. The first chapter addressing the facts that formed the development of the Municipal Plan of Education of the City of Carambeí - PR, discussing the implications of the historical, political and administrative process present in the constitution of this Parana city. In the second chapter we performed the analysis related to the preparation and execution of the Brazilian education system, considering the pacts signed at conferences in Jomtien (1990) and Dakar (2000). In The last chapter we analyzed some of the presence of neoliberal policies in the reform of the state apparatus, in order to expose the effect of the actions on the education planning in different scopes.